Elevated road segment (ERS) passage design may provide enhanced connectivity for amphibians, reptiles, and small mammals - Brehme, Cheryl S.; Barnes, Stephanie; Ewing, Brittany; Gould, Philip; Vaughan, Cassie; Hobbs, Michael; Tornaci, Charles; Holm, Sarah; Sheldon, Hanna; Fiutak, Jon; Fisher, Robert N. (Frontiers in Ecology and Evolution, 2023)
Designs for safe and effective road crossing structures for small animals are typically under-road microtunnels and culverts which have varying levels of effectiveness reported in the scientific literature. Many species, particularly migratory amphibians, may have limited ability to find and use passages if they are too far apart, resulting in substantial barrier effects. We designed a novel open elevated passage (elevated road segment: ERS), similar to a low terrestrial bridge, that could theoretically be built to any length based upon species needs and movement characteristics. A 30 m length prototype ERS was installed along a forest road with a history of amphibian road mortality in Sierra National Forest, California, USA. From 2018 to 2021, we monitored small animal activity under the ERS in relation to surrounding roadside and forest habitats using active infrared cameras. We documented a total of 8,815 unique use events, using species specific independence criteria, across 22 species of amphibians (3), reptiles (4) and small mammals (15). Results from Poisson regression modeling showed that amphibian activity was highest in the interior forest habitat, no habitat use differences were observed for reptiles, and small mammal activity was highest under the ERS. However, mean activity estimates under the ERS were equal to or greater than the open roadside habitat for all 22 species, suggesting that adding cover objects, such as downed logs and vegetation may further enhance passage use. Overall, results showed that the design of the ERS crossing has potential to provide high connectivity for a wide range of amphibian, reptile, and small mammal species while reducing road mortality. ERS systems can also be used in areas with challenging terrain and other hydrological and environmental constraints. Incorporating current road ecology science, we provide supplemental ERS concept designs for secondary roads, primary roads and highways to help increase the options available for road mitigation planning for small animals.